Mate Preference Plasticity in a Critically Endangered Frog: Implications for Conservation Breeding - Kelleher, Shannon R.; Silla, Aimee J.; Hertel, Anne G.; Dingemanse, Niels J.; Byrne, Phillip G. (Frontiers in Conservation Science, 2021)
Variation in female mate preferences for male traits remains poorly understood (both among and within females), despite having important evolutionary and conservation implications, particularly for captive breeding. Here, we investigate female mate preferences for male advertisement call frequency, and determine whether preferences vary over repeated trials, in the critically endangered southern corroboree frog, Pseudophryne corroboree. We conducted a series of phonotaxis trials in a six-speaker arena where naïve, captive-bred, virgin females were offered a choice between low, average and high frequency male advertisement calls, with a subset of females tested repeatedly. In the first trial, we found no evidence for a population-level preference for call frequency, but females spent less time in the low call zone than expected by chance. However, our results showed that female mate preferences changed over sequential trials. Females spent significantly more time in the low frequency call zone in the third trial compared to the first trial, and, in the last trial, females exhibited a significant population-level preference for low frequency calls. Subsequently, repeatability estimates of female preferences were low and did not significantly deviate from zero. Our results indicate that female P. corroboree mate preferences can exhibit temporal variation, and suggest that females are more attracted to low call frequencies after repeated exposure. These findings imply that female P. corroboree may become choosier over time, and highlight the potential for mate preferences to exhibit phenotypic plasticity within a single reproductive cycle. Overall, these findings provide the first information on mate preferences in P. corroboree, and emphasize the importance of considering individual variation in mate choice studies. From a conservation perspective, knowledge of individual variation in female mate preferences may be used to conduct behavioral manipulations in captivity that facilitate the breeding of genetically valuable individuals, and improve the success of conservation breeding programs.